Care and Concern: An Ethical Journey in Participatory Action Research - Stuart, Carol A. (Canadian Journal of Counselling and Psychotherapy, 2009)
The four basic principles of an ethical research framework, as outlined by the Code of Ethical Conduct for Research Involving Humans (1998), are reviewed in light of the requirements of a participatory action research approach. Literature on the ethics of participatory research is summarized as the backdrop»for a discussion about the ethical principle of care and concern within a participatory action research paradigm. It is argued that the ethics of morality and justice are appropriate, but insufficient, for participatory action research. The ethic of care obligates us to create improved conditions in the lives of those we join with in the research journey.